Bounds for Csiszár divergence and hybrid Zipf‐Mandelbrot entropy. (7th August 2019) - Adil Khan, Muhammad; Pečarić, Ðilda; Pečarić, Josip
Abstract : The purpose of this paper is to give a series of inequalities of the Jensen type and their applications for Csiszár divergence. By using these results, we give many estimations for hybrid Zipf‐Mandelbrot entropy.